Level of knowlegde of the women in the evaluation of the breast’s self-exam - Míria Conceição Lavinas Santos; Ana Fátima Carvalho Fernandes; Pacífica Pinheiro Cavalcanti (Rev Rene)
The study aims at to evaluate the knowledge degree on the breast’s self-exam (SEB) and the source where these women acquired this knowledge. We interviewed 141 women, assisted at a health center in the period of April and May of 2001. The results appear that 78 (55,3%), they knew how to describe the breast’s self-exam and 63 (44,7%), they didn’t know. Of the 78, that knew 27, (43,6%), they didn’t accomplish the practice. Regarding the knowledge source on SEB, TV was mentioned by 38, (48,7%), and prevention service for (28%). We conclued that is needed to develop strategies that mobilize the woman for the adoption of the self-help in relation to the practice of the SEB.